PEMILIHAN KODE PADA MAHASISWA RIAU DI YOGYAKARTA: KAJIAN SOSIOLINGUISTIK - Mahsusi, Juni; Djatmika, Djatmika; Marmanto, Sri (LINGUA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This study aims to identify kinds of codes and to uncover the factors that affect the code selection in the interactions among Riau students staying in in Yogyakarta. Sociolinguistic approach is used in this study.Â  Informants of this study are students from Riau staying in Yogyakarta. This study employed purposive sampling techniques and data were collected using observation, records and interview. The data were analyzed using the communication ethnography techniques adapted from Dell Hymes. The results showed that the first code in the interactions were: Indonesian language, mixing language, Malay language and foreign language, i.e. Arabic and English. The mixing language occurred in terms of code mixing and code switching. The dominant codes are those of Indonesian language and Malay language. Settings, participants, and topics are primary factors why a code is intended to choose.Â Â